Macrophages and Galectin 3 Control Bacterial Burden in Acute and Subacute Murine Leptospirosis That Determines Chronic Kidney Fibrosis - Ferrer, María F.; Scharrig, Emilia; Charo, Nancy; Rípodas, Ana L.; Drut, Ricardo; Carrera Silva, Eugenio A.; Nagel, Ariel; Nally, Jarlath E.; Montes de Oca, Daniela P.; Schattner, Mirta; Gómez, Ricardo M. (Frontiers in Cellular and Infection Microbiology, 2018)
Previous studies have suggested that macrophages may contribute to acute Leptospira dissemination, as well as having a major role in kidney fibrosis. Our aim was to characterise the role of macrophages and galectin 3 (Gal-3) on the survival, clinical course, bacterial burden, interstitial nephritis, and chronic kidney fibrosis in Leptospira interrogans serovar Copenhageni (LIC)-induced experimental murine leptospirosis. C57BL/6J mice depleted of macrophages by liposome-encapsulated clodronate treatment and infected with LIC presented a higher bacterial burden, had reduced subacute nephritis and enhanced chronic kidney fibrosis relative to untreated, infected mice. Moreover, LIC infection in mice whose Gal-3 was disrupted (Lgals3-/-) had a higher bacterial burden and enhanced subacute nephritis and chronic kidney fibrosis when compared to C57BL/6J wild-type mice. Chronic fibrosis did not correlate with higher transcription levels of TGF-β1 or IL-13 in the kidneys. Kidney fibrosis was found in chronically infected rats as well as in wild infected rats. On the other hand, human fibroblast cultures exhibited enhanced differentiation to myofibroblasts after treatment with LIC. Our results demonstrate that macrophages and Gal-3 play a critical role in controlling the LIC burden but has a minor role in subsequent fibrosis. Instead, kidney fibrosis was better correlated with bacterial burden. Taken together, our results do not support a role for macrophages to disseminate leptospires during acute infection, nor in chronic kidney fibrosis.